Clinical course and outcomes of confirmed and suspected Pneumocystis jirovecii pneumonia in Sowetan children living with HIV - Darji, Mohiniben (University of the Witwatersrand, Johannesburg, 2022)
Introduction: Pneumocystis jirovecii is an important opportunistic pathogen in children living with HIV (CLWH), responsible for the majority of community acquired pneumonia (CAP) admissions in infancy. There is scanty evidence on long-term survival rates in children hospitalised with P. jirovecii pneumonia (PCP), especially in settings with a high burden of paediatric HIV. Methods: Admissions to general paediatric wards at Chris Hani Baragwanath Academic Hospital over the period 01 January 2011 to 31 December 2019 were assessed for a discharge diagnosis of PCP. PCP was classified as being confirmed or presumed, based on laboratory criteria. Only CLWH were included in the study. Results: Over the 9-year study period, 390 cases of PCP were diagnosed, of which 297 (76.2%) were in CLWH. The majority of the PCP episodes were presumed (262/297, 88.2%). Sixteen children had recurrent PCP admissions. There was no difference between the median age of children at admission with confirmed PCP or presumed PCP (4.07 months vs 3.66 months; P=0.590). Children with presumed PCP were significantly underweight (weight-for-age Z-score -2.88 vs -1.74; P<0.001) and wasted (weight-for-length Z-score -1.15 vs -0.38; P=0.039) compared to those with confirmed PCP. Children with presumed PCP had a higher prevalence of confirmed pulmonary tuberculosis (7/18 (38.9%) vs 1/35 (2.9%); P=0.002). The majority (56.1%) of patients were initiated on antiretroviral therapy (ART) one week after the PCP admission episode. Of 58 PCP episodes in which data on mechanical ventilation was available, 18 (31.0%) were ventilated. Case fatality was 44.4% in ventilated patients, and the overall in-hospital case fatality was 24.8%. One-hundred, twenty-five children were followed up at the outpatient ART Clinic, of which 42 (33.6%) were still in care at the end of the study. The median duration of co-trimoxazole preventive therapy was 1278 days. Conclusion: PCP was often the first presentation of HIV infection. Children with PCP still have poor outcomes. Despite the decline in PCP admissions, there was a high in-hospital mortality rate.
A Research Report submitted in partial fulfillment of the requirements for the degree of Masters of Medicine in Paediatrics, to the Faculty of Health Sciences, School of Clinical Medicine, University of the Witwatersrand, Johannesburg, 2022.
Keywords: PCP - Pneumocystis jirovecii pneumonia; CPT - Co-trimoxazole prophylaxis treatment; CLWH - Children living with HIV; UCTD; SDG-3: Good health and well-being; SDG-4: Quality education